Border Temporalities of an Old Letter. A Hermeneutic Interpretation of Cross-Border Veteran Welfare - Venken, Machteld (Borders in Globalization Review, 2024)
Abstract: „The article uses the concept of border temporalities to offer a hermeneutic interpretation of an old letter containing a request from a cross-border female migrant from Luxembourg to access French welfare benefits. In doing so, it systematically unravels the way in which time was lived and experienced differently by borderland residents as opposed to French lawmakers. The alternative temporality characterizing the third space of the Luxembourgian–German– French borderlands clashed with the spatio-temporal hierarchy imposed by France in the period after the First World War to exclude the majority of people living abroad from access to social provision. The article concludes its hermeneutic circle with a reflection on how historical research on borders and borderlands is conditioned by the temporality of archives and the temporality of research funding.“
Keywords: Archiv; Frau; Fremdheit; Geschichtsschreibung; Grenzgebiet; Hermeneutik; Veteran

Un projet de guide de sources transfrontalières franco-belges - Nuyttens, Michel (Liber Amicorum Alfred Minke, 2011)
Keywords: Archiv; Archivkunde

Archivalien zum Thema „Grenzen“ im Staatsarchiv Münster - Knackstedt, Wolfgang (Grenzen komen en gaan, kommen und gehen, 1993)
Keywords: Archiv; Grenzgebiet; Hochstift Münster (Westf)

Bronnen met betrekking tot wisselende grenzen in het Rijksarchief in Gelderland - Wouters, Peter (Grenzen komen en gaan, kommen und gehen, 1993)
Keywords: Archiv; Grenzgebiet; Provinz Geldern; Staat Geldern